Preparticipation injury complaint is a risk factor for injury: a prospective study of the Moscow 2013 IAAF Championships - Alonso, J.-M.; Jacobsson, J.; Timpka, T.; Ronsen, O.; Kajenienne, A.; Dahlström, Ö.; Spreco, A.; Edouard, P. (British Journal of Sports Medicine, 2015)
Objectives: To determine the health status of athletes before the start of an international athletics championship and to determine whether preparticipation risk factors predicted in-championship injuries. Methods At the beginning of the 2013 International Association of Athletics Federations (IAAF) World Championships, all registered athletes (n=1784) were invited to complete a preparticipation health questionnaire (PHQ) on health status during the month preceding the championships. New injuries that occurred at the championships were prospectively recorded. Results The PHQ was completed by 698 (39%) athletes; 204 (29.2%) reported an injury complaint during the month before the championships. The most common mode of onset of preparticipation injury complaints was gradual (43.6%). Forty-nine athletes in the study reported at least one injury during the championships. Athletes who reported a preparticipation injury complaint were at twofold increased risk for an in-championship injury (OR=2.09; 95% CI 1.16 to 3.77); p=0.014). Those who reported a preparticipation gradual-onset injury complaint were at an almost fourfold increased risk for an in-championship time-loss injury (OR=3.92; 95% CI 1.69 to 9.08); p=0.001). Importantly, the preparticipation injury complaint severity score was associated with the risk of sustaining an in-championship injury (OR=1.14; 95% CI 1.06 to 1.22); p=0.001). Summary and conclusions About one-third of the athletes participating in the study reported an injury complaint during the month before the championships, which represented a risk factor for sustaining an injury during the championship. This study emphasises the importance of the PHQ as a screening tool to identify athletes at risk of injuries before international championships.